Pengaruh Corporate Social Responsibility (CSR) PT. Lintas Marga Sedaya terhadap Pembentukan Citra Perusahaan pada Masyarakat sekitar Tol Cipali - Nurfitriana Novitasari Iskandar (UPT Publikasi Ilmiah UNISBA, 2024)
Corporate image is how the public perceives external communication efforts through an organisation that functions as a public response to the activities carried out by the company. This study aims to explain and analyse the influence of PT. Lintas Marga Sedaya's corporate social responsibility (CSR) on the formation of corporate image among the community surrounding the Cipali Toll Road. This study is an explanatory survey. The variables in this study are Environmental Protection (X1), Charity Work (X2), Urban Development (X3), Investment in Local Businesses (X4), Employee-Oriented Projects (X5), Knowledge (Z1), Perception (Z2), Motive (Z3), and Emotion (Z4) simultaneously have a significant effect on Corporate Image (Y), with the population being the community living around the Cipali toll road and the sampling technique being cluster random sampling. The analysis technique used is path analysis. The results of this study show that 1) investment in local businesses (X4) and employee-oriented projects (X5) have a significant effect on company image (Y). 2) Environmental protection (X1), charity work (X2), and urban development (X3) do not have a significant effect on company image (Y). 3) Environmental protection (X1), charitable work (X2), urban development (X3), investment in local businesses (X4), employee-oriented projects (X5), knowledge (Z1), perception (Z2), motive (Z3), and emotion (Z4) simultaneously have a significant effect on company image.